Criminogenic needs based on sexual assault typologies - Thomas, Mackenzie (My University, 2022)
People have an intrinsic desire to understand other people’s behaviour, especially when considered socially deviant or abnormal. This fascination has led to several theoretical and empirically-based typologies for criminal behaviour, including sexual assault. These are typically based on the premise that those who commit sexual assault have different individual characteristics. The greater knowledge we gain to identify diverse groups of these individuals may help us understand the characteristics associated with their sexual offending. The current study examines the typology proposed by Knight and Prentky (1990). The Massachusetts Treatment Center Rapist Typology, Version 3 (MTC: R3) identifies five general categories of rapists, four of which are examined in the current study. These categories include opportunistic, pervasively angry, vindictive, and sexual types. Using a sample of 300 individuals who have been investigated for sexual assault, the present study categorizes these individuals into one of these typologies. This research identifies potentially unique attributes for each subtype, and it is hypothesized that these subtypes will present with different individual characteristics, including criminogenic needs, depending on the type of motivation that reflects a particular individual who sexually offends. The practical implications of this study for criminal justice professionals, such as police, will be discussed, and it is hoped that our findings will increase our understanding of individuals who have committed sexual offences.
Presented on September 29-October 1, 2022 at the Association for the Treatment of Sexual Abusers 40th Annual Research and Treatment Virtual Conference.
Keywords: sex offenders; criminal behavior, prediction of